A Single Bout of Fatiguing Aerobic Exercise Induces Similar Pronounced Immunological Responses in Both Sexes - Lobo, Lázaro Fernandes; Morais, Mariana Gomes de; Marcucci-Barbosa, Lucas Soares; Martins-Junior, Francisco de Assis Dias; Avelar, Luíza Martino; Vieira, Erica Leandro Marciano; Aidar, Felipe J.; Wanner, Samuel Penna; Silva, Lucélia Scarabeli; Noman, Maria Clara; Camargos, Bruno Muzzi; Freitas, Kátia Michelle; et al. (Frontiers in Physiology, 2022)
Introduction: Physical exercise can acutely and chronically modulate immunological responses. Women and men have different innate and adaptive immune responses, and in this sense, these two groups may also have different acute immunological responses induced by exercise. In addition, it is essential to understand further whether the effects of physical exercise on the immune system responses depend on sex because limited scientific evidence on this topic is available. This information may allow athletes and coaches to improve the training process, mainly to understand if the physiological impact of given training stimuli in women is similar to that in men. Objective: The present study aimed to investigate the acute effects of continuous submaximal exercise until fatigue on physiological and immunological parameters in amateur female and male runners. Methods: This study included 18 female and 15 male volunteers. Each participant visited the laboratory on four consecutive days. The first visit consisted of medical history taking and explaining the study design. On the second visit, the participants were subjected to an incremental test to determine their maximal rate of oxygen consumption (VO2max) that was required to prescribe the intensity of the submaximal exercise protocol. On the third visit, the fatiguing exercise protocol was performed at 77%–80% of the VO2max. During this submaximal exercise, the heart rate, rating of perceived exertion (RPE), and blood lactate were recorded. Blood samples were collected before, immediately after, and 1 h after the fatiguing protocol to analyze the plasma levels of cytokines and creatine kinase (CK) and to count leukocytes. Finally, on the fourth visit, the participants underwent physical evaluations to measure their body composition using dual-energy X-ray absorptiometry (DXA) imaging. Results: The average ages of the female and male groups were 34.2 ± 3.7 and 30.5 ± 4.3 years old, respectively. The female group ran 57 ± 27 min, while the male group ran 52 ± 15 min before fatiguing. In the female group, when comparing before and after the submaximal exercise, marked increases were observed in the following variables: heart rate (from 68.5 to 180.4 bpm), RPE (from 3.6 to 8.2), lactate (from 2.1 to 4.49 mmol/L), and CK (from 89.5 to 126.3 U/L). In addition, the female group showed an increased number of total leukocytes (from 7222.3 to 11162.9 × 106/μl), neutrophils (from 4,403 to 6,480 × 106/μl), and lymphocytes (from 2,342 ± to 3,562 × 106/μl) from pre- to post-submaximal exercise. In the male group, similar elevations in psychophysiological variables were observed, as evidenced by comparing the heart rate (from 52.8 to 184.1 bpm), RPE (from 0.0 to 8.9), lactate (from 2.7 to 7.2 mmol/L), and CK (from 106.2 to 165 U/L) before and after the submaximal exercise. The male group also showed an augmented number of total leukocytes (from 6,245 to 8,050 × 106/μl), neutrophils (from 3,335 to 4,128 × 106/), and lymphocytes (from 2,191 to 3,212 × 106/μl) when comparing pre- and post-submaximal exercise. There were no differences in the changes between women and men for these parameters. Conclusion: The aerobically fatiguing exercise protocol induced pronounced changes in the heart rate, plasma levels of lactate and CK, total leukocyte count, especially the number of neutrophils and lymphocytes, in both sexes. The fatiguing exercise protocol also changed the plasma levels of IL-6 and IL-10 in the female and male groups. Under the present conditions, the physiological changes induced by fatiguing submaximal exercise, including the immunological changes, were not influenced by sex. This study shows that the same aerobic physical exercise can alter immunological parameters in women and men, and this response is similar between sexes.